Development of the external male and female genitalia in the immature stages of Cicadellidae (Homoptera) - Kathirithamby, J. (Wiley, 1974)
Up to date studies on the development of the external male and female genitalia in Cicadellidae are somewhat limited. Hackman (1922) described the male and female genitalia in Cicadella. hieroglyphica Say, and Singh Puthri (19241 has given a brief description of the development of the male genitalia of Idiocerus. This paper presents a detailed study of the development of the various parts of the external male and female genitalia in fivespecies of Cicadellidae: Ulopa reticulata (F.), Doratura stylata (Boheman), Cicadula persimilis (Edwards), Mocydiopsis parvicauda Ribaut, Balclutha punctata (Thunberg), and Zygina scutellaris (Herrich-Schaeffer). The various instars were reared in the laboratory and specimens were fixed and mounted unstained for microscopic examination.